Nester's Microbiology : a human perspective - Anderson, Denise G., ....-; Salm, Sarah, ....-; Beins, Mira, ....- (New York : Mc.Graw-Hill, 2022)
Perfect for the non-major/allied health student (and also appropriate for mixed majors courses), this text provides a rock solid foundation in microbiology. By carefully and clearly explaining the fundamental concepts and offering vivid and appealing instructional art, Microbiology: A Human Perspective draws students back to their book again and again!
Keywords: Microbiologie